Triple Probe Measurements Benchmarked by Interferometry in a Pulsed‐Power Plasma. Issue 1 (9th January 2013) - Mackel, F.; Kempkes, P.; Tenfelde, J.; Ridder, S.; Soltwisch, H.
Abstract An electrostatic triple probe was employed to investigate electron densities in a pulsed‐power discharge plasma. The inherent property of electrostatic probes to disturb the plasma is one of the major problems of these diagnostics. The quantification of the systematic error is not straightforward. In order to get non‐intrusive and reliable measurements, a CO2 laser interferometer was set up to determine line integrated‐electron densities. The data are converted into electron number densities by assuming a parabolic density distribution across the plasma column. In a comparison, the triple probe underestimates the electron density (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)